Drosophila as a Model System to Investigate the Effects of Mitochondrial Variation on Innate Immunity - Salminen, Tiina S.; Vale, Pedro F. (Frontiers in Immunology, 2020)
Understanding why the response to infection varies between individuals remains one of the major challenges in immunology and infection biology. A substantial proportion of this heterogeneity can be explained by individual genetic differences which result in variable immune responses, and there are many examples of polymorphisms in nuclear-encoded genes that alter immunocompetence. However, genetic polymorphism in an additional genome, inherited maternally inside mitochondria (mtDNA), has been relatively understudied. Mitochondria are increasingly recognized as important mediators of innate immune responses, not only because they are the main source of energy required for costly immune responses, but also because by-products of mitochondrial metabolism, such as reactive oxygen species (ROS), may have direct microbicidal action. Yet, it is currently unclear how naturally occurring variation in mtDNA contributes to heterogeneity in infection outcomes. In this review article, we describe potential sources of variation in mitochondrial function that may arise due to mutations in vital nuclear and mitochondrial components of energy production or due to a disruption in mito-nuclear crosstalk. We then highlight how these changes in mitochondrial function can directly impact immune responses, focusing on their effects on ATP- and ROS-generating pathways, as well as immune signalling. Finally, we outline how being a powerful and genetically tractable model of infection, immunity and mitochondrial genetics makes the fruit fly Drosophila melanogaster ideally suited to dissect mitochondrial genetic effects on innate immune responses to infection.